Usaha Meningkatkan Konsep Diri yang Positif Siswa Kelas XII TKJ 2 SMKN 2 Pinrang Melalui Konseling Peer Group - Dahlia Haruna (IAIN Ambon, 2017)
The objectives of this research are (i) to improve the ability of forming positive self concept on the students of class XII TKJ 2 SMK Negeri 2 Pinrang, (ii) students able to improve positive self concept after guidance and counseling process through peer group counseling. This research is guidance and counseling research. This research uses Kemmis and Mc Taggart model which consist of four stages: (i) planning, (ii) Action, (iii) Observation, (iv) Reflection (reflection). The subjects of the research are the students of class XII TKJ 2 SMK Negeri 2 Pinrang. Data were analyzed using descriptive analysis. The results showed that: (i) the application of peer group counseling in the process of guidance and counseling services can improve students' positive self concept in the students of class XII TKJ 2 SMK Negeri 2 Pinrang in the first cycle by 8.66% and increase again by 11.46 % after the second cycle of action, and (ii) through the application of peer group counseling, trained and skilled students to work with friends in solving problems.